PENGGUNAAN CARBOXYMETHYL CELLULOSE DAN KARAGENAN SEBAGAI PENSTABIL DALAM PEMBUATAN ES KRIM WORTEL. - Rifhatia Faiza Faiza Amhary; Rahmayuni Rahmayuni; Yelmira Zalfitri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
The aim of this study was to obtain the best type of stabilizer for the quality of ice cream produced. This research was conducted experimentally using a randomized complete design with five treatments and three replications, followed by the DNMRT test at 5% level. The treatments in this study were  CK1 = CMC and carrageenan (0 : 1), CK2 = CMC and carrageenan (1 : 0), CK3 = CMC and carrageenan (1 : 1), CK4 = CMC and carrageenan(1 : 2), CK5 = CMC and carrageenan (2 : 1). The parameters observed include overrun, melting time, total solids, fat content, protein content and sensory assessment in a descriptive and hedonic analysis (color, aroma, taste, texture). The results showed that the best treatment was CK5 = CMC and carrageenan (2 : 1) treatment with an overrun value of 25,51%, melting time of 20,16 minutes, total solids of 32,12%, fat content of 4,17%, protein content of 2,75%. The hedonic assessment result showed that the panelist liked the product, with a descriptive assessment that is yellow, a slightly carrot-scented aroma, sweet taste, soft texture. Keywords: ice cream, carrots, stabilizer.